2020
DOI: 10.1021/acs.energyfuels.0c02257
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Combustion Characteristics of Bio-Oils from Catalytic Co-Pyrolysis of Grape Seeds, Polystyrene, and Waste Tires

Abstract: This work aims to study the bio-oils obtained from the catalytic co-pyrolysis of waste polymers and a residual biomass (grape seeds, GS). For that purpose, the organic liquid fractions produced in an auger reactor were thoroughly characterized in two steps, obtaining in the first place their main physicochemical properties as well as their chemical compositions, and second, their droplet combustion behaviors. Both the polymer type (waste tires or polystyrene, WT and PS, respectively) and the nature of the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, catalytic co-pyrolysis increased solid-phase CO 2 formation by up to 3 wt.% in the presence of 10 wt.% of PS. Another study on co-pyrolysis of grape seeds and PS was performed by Muelas et al [ 145 ], using Carmeuse as a catalyst, differentiating it from the previous one mentioned. Their experiments were performed at a GS: PS ratio of 80:20 in an auger reactor; the authors found that a significant improvement in the physicochemical properties of the bio-oils was obtained when using a catalyst with lower viscosity, density, and oxygen content.…”
Section: Statistical Analysis Of Ps Pyrolysismentioning
confidence: 99%
“…However, catalytic co-pyrolysis increased solid-phase CO 2 formation by up to 3 wt.% in the presence of 10 wt.% of PS. Another study on co-pyrolysis of grape seeds and PS was performed by Muelas et al [ 145 ], using Carmeuse as a catalyst, differentiating it from the previous one mentioned. Their experiments were performed at a GS: PS ratio of 80:20 in an auger reactor; the authors found that a significant improvement in the physicochemical properties of the bio-oils was obtained when using a catalyst with lower viscosity, density, and oxygen content.…”
Section: Statistical Analysis Of Ps Pyrolysismentioning
confidence: 99%
“…With the rise in interest in biomass pyrolysis, numerical modeling studies have been conducted to investigate the process at different scales. These scales range from the molecular level and reaction kinetics to the reactor level for estimating product compositions [81][82][83]. Although multi-scale investigations are crucial, the input parameters from the molecular and particle scales are elementary and require integration with reactor levels for designing, scaling up, and optimizing industrial applications.…”
Section: Analysis Of Cfd Studiesmentioning
confidence: 99%
“…Recovering these wries will lead to more than 1 million tons of recycled steel each year globally, helping to conserve 1.1 million tons of iron ore, 0.6 million tons of coking coal, and 0.05 million tons of limestone . More examples of TDP include new tires, rubber walkways, playground mulch, synthetic turf, and sports surfaces. The second category is energy recovery or tire-derived fuels (TDF), where ELT are used as an alternative fuel source . The third category of ELT recovery is civil engineering, where ELT are repurposed for applications such as breakwaters and coastal protection, erosion barriers, ground improvement, landfill construction (as a lightweight backfill in gas venting systems, in leachate collection systems and operational liners, and for capping and daily cover), slope stabilization and retaining walls, , sound barriers and insulation applications, stormwater infiltration galleries, railroad ties, and roads …”
Section: Introductionmentioning
confidence: 99%